2021
DOI: 10.3390/plants10040665
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Origin and Diversity of Croatian Common Bean Germplasm Using Phaseolin Type, SSR and SNP Markers and Morphological Traits

Abstract: Landraces represent valuable genetic resources for breeding programmes to produce high-yielding varieties adapted to stressful environmental conditions. Although the common bean (Phaseolus vulgaris L.) is an economically important food legume for direct human consumption worldwide, common bean production in Croatia is based almost exclusively on landraces and there is no common bean breeding program. Information on phaseolin type and results of population structure and genetic diversity obtained by analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
1
9
1
Order By: Relevance
“…Phaseolin is an important and informative biochemical marker for studying the genetic diversity in bean germplasms (Vidak et al., 2021). Here, only eight phaseolin patterns were detected using SDS‐PAGE gel electrophoresis (Table 7), which was significantly less than the 18 phaseolin patterns present in the diversity center of the common bean.…”
Section: Discussionmentioning
confidence: 99%
“…Phaseolin is an important and informative biochemical marker for studying the genetic diversity in bean germplasms (Vidak et al., 2021). Here, only eight phaseolin patterns were detected using SDS‐PAGE gel electrophoresis (Table 7), which was significantly less than the 18 phaseolin patterns present in the diversity center of the common bean.…”
Section: Discussionmentioning
confidence: 99%
“…This result supports the proven predominance of the Andean genotypes over the Mesoamerican examples in the Mediterranean Basin. Furthermore, a prevalence of C-type over T-type phaseolin has been reported in Italian and European common bean landraces [ 48 , 49 ], while the H-type phaseolin has proven to be more unusual among the common bean populations in Europe [ 22 ]. Moreover, it has been found that cultivars belonging to the Mesoamerican gene pool show small or medium-sized seeds (<25 g or 25–40 g/100-seed weight), while their Andean counterparts have larger seeds (>40 g/100-seed weight) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They can also show resilience by tolerating a spectrum of biotic and abiotic stress factors, demonstrating their adaptability and robustness under different environmental conditions. Although these populations are under the influence of human selection and environmental stresses, they have existed for a long time, and heterogeneity within these populations appears to be an important adaptive trait ( Figure 1 ) [ 36 , 49 , 50 ]. Landraces are also not formally improved and are adapted to the specific habitat in which they are grown.…”
Section: Seed Heterogeneity Phenomenon In Common Beansmentioning
confidence: 99%
“…Landraces are also not formally improved and are adapted to the specific habitat in which they are grown. They are grown and maintained by local farmers, so there are even different varieties with similar traits but different names in each location [ 7 , 25 , 34 , 36 , 50 ]. They are often cultivated and maintained by older farmers, with little or no support from state or local institutions.…”
Section: Seed Heterogeneity Phenomenon In Common Beansmentioning
confidence: 99%